Strategy for Improving the Quality of Non-Formal Education in the Field of Equality Programs in the Context of Policy and Implementation - Yayat Hidayat; Tb. Abin Syamsudin; Dede Khoeriah; Yosal Iriantara (Tarbawi, 2021)
This research is motivated by the problems faced in implementing the equivalence program in non-formal education in the city of Bandung. The objectives of this research were: (1) to analyze the strategy for improving the quality of non-formal education equality programs in the context of policy and implementation; (2) assessing the implementation of the PNF equivalency program quality improvement in the context of policy and implementation; (3) knowing the effect of policies and implementation in order to improve the quality of the equality program PNF; (4) examines the problems faced to improve the quality of the equality PNF program in the context of policy and implementation; (3) knowing solutions and improvement efforts on how to improve the quality of PNF equality programs in the context of policy and implementation. This research uses mixed methods, extracting data through questionnaire techniques, interviews, observation, and documentation. The data analysis technique used in this study was parametric statistics consisting of multiple linear regression and significance tests with multiple correlations. The results showed that the strategy to improve the quality of the equality program PNF had been implemented but not maximized, not synergized, and not simultaneous. Strategies are implemented in coaching, training, courses, meetings, and outreach to PKBM managers, PKBM heads, and tutors. Policies in the form of regulations have been implemented, there is a correlation, but the contribution is not yet maximal. It can be seen from the implementation of coaching, which is sometimes carried out, partly because of the lack of funds for coaching programs. Based on the research results, it can also be seen that there is a positive effect of policies on improving the quality of the equivalence program, but the positive effect of increasing the quality is not yet maximal.